Identification of Immunoglobulin Gene Usage in Immune Repertoires Sequenced by Nanopore Technology - Ahumada-Garcia, Roberto; Gonzalez-Puelma, Jorge; Alvarez-Saravia, Diego; Barrientos, Ricardo J.; Uribe Paredes, Roberto Alex; Lopez-Cortes, Xaviera A.; Navarrete Signorile, Marcelo Alejandro (My University, 2019)
The immunoglobulin receptor represents a central molecule in acquired immunity. The complete set of immunoglobulins present in an individual is known as immunological repertoire. The identification of this repertoire is particularly relevant in immunology and cancer research and diagnostics. In a seminal work we provided a proof of concept of the novel ARTISAN-PCR amplification method, we adapted this technology for sequencing using Nanopore technology. This approach may represent a faster, more portable and costeffective alternative to current methods. In this study we present the pipeline for the analysis of immunological repertoires obtained by this approach. This paper shows the performance of immune repertoires sequenced by Nanopore technology, using measures of error, coverage and gene usage identification. In the bioinformatic methodology used in this study, first, Albacore Base calling software, was used to translate the electrical signal of Nanopore to DNA bases. Subsequently, the sequons, introduced during amplification, were aligned using bl2seq from Blast. Finally, selected reads were mapped using IMGT/ HighV-QUEST and IgBlast. Our results demonstrate the feasibility of immune repertoire sequencing by Nanopore technology, obtaining higher depth than PacBio sequencing and better coverage than pair-end based technologies. However, the high rate of systematic errors indicates the need of improvements in the analysis pipeline, sequencing chemistry and/or molecular amplification.
Keywords: immunoglobulin; sequencing; data analysis; nanopore; pipeline